Strategy For Empowering Tourist Village Communities Towards Sustainable Communities In Bongkasa Pertiwi, Badung - Angel Pricilia Pinontoan; Dapar, Angel Melody Filleony Rut; Silitonga, Duma Theresia; Putra, I Nyoman Triana; Darsana, I Made; Putra, Dewa Putu Kiskenda Erwanda (Brilliant International Journal Of Management And Tourism, 2025)
This study examines the development of community-based tourism villages as a foundation for sustainable development aligned with the Sustainable Development Goals (SDGs). Bongkasa Pertiwi Tourism Village in Badung Regency has significant tourism potential, but its community empowerment strategies are suboptimal. The objectives of this study include analyzing the implemented empowerment strategies, identifying supporting and inhibiting factors, and evaluating the strategies' contribution to the formation of a sustainable community. Using a qualitative approach, the study involved village communities, tourism managers, and the local government as key informants. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that empowerment strategies include capacity building training, strengthening village institutions, and developing local culture-based attractions. The main supporting factors are community solidarity, government support, and natural and cultural potential. Conversely, limited human resources (HR), access to funding, and suboptimal promotion are inhibiting factors. Nevertheless, the empowerment strategies in Bongkasa Pertiwi have positively contributed to sustainable community development, although further managerial and economic optimization remains crucial.